Effectiveness of an educational video on concussion knowledge in minor league hockey players: a cluster randomised controlled trial - Cusimano, M. D.; Chipman, M.; Donnelly, P.; Hutchison, M. G. (British Journal of Sports Medicine, 2014)
Background: With the heightened awareness of concussions in all sports, the development and implementation of effective prevention strategies are necessary. Education has been advocated as an effective injury prevention intervention.Purpose To examine the effectiveness of the `Smart Hockey: More Safety, More Fun` video on knowledge transfer among minor league hockey players. Study Design: Cluster-randomised controlled trial.Methods A total of 267 participants from two age divisions and competitive levels were assigned to either a video or no-video group. The video was shown (or not shown) to the entire team as a result of random assignment. To evaluate the effectiveness of the educational video, questionnaires specific to concussion knowledge and players` attitudes and behaviours were completed. Results: There was a significant increase in the players` concussion knowledge scores immediately following exposure to the video (F(1,103)=27.00, p<0.001). However, concussion knowledge at 2 months was not significantly different between the video and no-video groups, after controlling for prior knowledge level, age and competitive level (F(1,115)=0.41, p=0.523). Similarly, players` attitudes and behaviour scores at 2 months did not differ between groups (F(1,115)=0.41, p=0.507). Conclusions: We were able to show that a single viewing of an educational video in hockey could immediately improve knowledge about concussion but that this effect was transient and lost at 2-month follow-up. Future prevention endeavours in hockey and other sports should attempt to incorporate strategies and modalities to enhance knowledge retention.